Lung consolidation caused by Mycoplasma hyopneumoniae has a negative effect on productive performance and economic revenue in finishing pigs - Ferraz, M. E.S. [UNESP]; Almeida, H. M.S. [UNESP]; Storino, G. Y. [UNESP]; Sonálio, K. [UNESP]; Souza, M. R.; Moura, C. A.A.; Costa, W. M.T.; Lunardi, L.; Linhares, D. C.L.; de Oliveira, L. G. [UNESP] (Elsevier, 2020)
This study aimed to measure the impact of productivity and the consequent economic losses related to lung lesions caused by M. hyopneumoniae. Five-hundred 75 days-old pigs were selected and weighed at the beginning and at the end of the finishing phase to assess the average daily gain (ADG). These animals were evaluated at the slaughter, and samples were collected for laboratory analysis to confirm the presence of M. hyopneumoniae DNA. The lungs of each pig were examined and classified into groups based on the extension of macroscopic lung lesions. Four-hundred eighty-six lungs were examined and 68.5 % (n = 333) had macroscopic lung lesions. All pigs with lesions were positive for M. hyopneumoniae in qPCR. Linear mixed regression models (proc Glimmix) were performed on SAS to estimate the effect of macroscopic lung lesion scores on the ADG of finishing pigs. All pairwise comparisons among lesion score groups were performed using p < 0.05. For each increase of one percent in the lesion area, there was a decrease of 1.8 g in the daily weight gain. All the groups had a numerically lower ADG when compared to Group 1 (no lesions). The economic analysis was performed by simulation on Excel to estimate and compare the financial performance of the different lung lesion score groups. The negative correlation found between the group with no lung lesions and the group with more than 15.1 % of lesions, showed a statistical difference in ADG, which could mean an opportunity to gain up to $ 6.55 per pig at slaughter. The presence of lesions causes the animals to decrease their productive potential, causing financial loss and generating impacts on the production system.
Keywords: ADG; Enzootic pneumonia; Financial losses; qPCR; Slaughter